Influencia de la tecnología en el estilo de vida de un niño de segundo de básica - Jara Arbelae, Melissa (2020)
This research work entitled technology in lifestyle. Situation that had the following problem as a general problem Influence of technology on the lifestyle of the second-grade children, As a general objective. To determine the Influence of technology on the lifestyle of the second-grade children. The methodological processes, for the collection of the information was of a basic and descriptive and correlational type, its design was non-experimental, field and bibliographic, the methodology applied was the analytical inductive methods, which allowed the confrontation of the different theories that were selected and validated to describe the variables and structure the theoretical support. It was also considered a population of 1, a boy named José person involved in the problem. For this, the following techniques were applied, such as observation, interview and several tests through a questionnaire that were the instruments that were used to obtain the information required for the investigation. Process that allowed the analysis of the results that allowed to make and reach the conclusion of said research work showing the problem posed.